A model to integrate ecosystem services into spatial planning: Ria de Aveiro coastal lagoon study. (1st September 2020) - Sousa, Lisa P.; Alves, Fátima L.
Abstract: The need to bring ecosystem services into strategic decisions and policy design for the governance of social-ecological systems is found to be mutually advantageous within the scientific and political community, as it may lead to better environmental decision-making and promote sustainable development. However, its actual integration into spatial planning and decision-making processes have not been fully realised and face substantial challenges, particularly regarding the marine environment. This paper uses the Ria de Aveiro coastal lagoon (Vouga estuary, Portugal) and the conceptual framework of Estuary Programmes as a starting point for proposing a model for the gradual incorporation of ecosystem services into policy and decision-making processes. Estuaries are complex social-ecological systems that lay at the interface between marine and terrestrial ecosystems, which are managed through Estuary Programmes – a special programme of strategic nature that aim to protect the natural resources of estuary and estuary banks. Despite having a legal framework since 2009, Estuary Programmes have never been developed, posing an opportunity for improving traditional practices and adapting them according to new methodologies and approaches. The proposed model, with three essential stages, provides a way forward for strengthening the process of environmental planning and management towards sustainability, territorial and social cohesion, responding to current societal challenges and contributing to human well-being. Principles such as comprehensive, adaptive, inclusive, and integrative were established as key for guiding ecosystem services integration into the spatial planning process. Graphical abstract: Image 1 Highlights: ES are crucial to support decision-making, environmental management, and strategic planning. The development of Estuary Programmes is a good opportunity to test EBA and improve traditional planning practices. Data availability and absence of agreement on standard methods should not hinder ES integration. The proposed model strengths the planning process towards sustainability, territorial and social cohesion. Four key principles for ES integration into spatial planning processes: comprehensive, adaptive, inclusive, integrative.